THEORETICAL ANALYSIS OF THE PHENOMENA IN THE STRUCTURE OFHYPOCHONDRIAC DISORDER - Hugasiyan-Hachmeryan, Anitsa (E-Journal VFU, 2024)
The article considers the main moments of origin, history and spread ofhypochondria as a psychosomatic disease. Emphasis is placed on features such as the clinicalpicture, neurotic components, depressive aspects affecting the overall personal functioning ofhypochondria sufferers, as well as self-suggestion with unreasonable concern for their ownhealth of persons suffering from this specific psychosomatic disorder.
Keywords: fear; depression; OCD (obsessive compulsive disorder); psychosomatic illness; hypochondria